2009
DOI: 10.28945/81
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise E-Learning Success Factors: An Analysis of Practitioners’ Perspective (with a Downturn Addendum)

Abstract: This study proposes nine success factors for enterprise-wide e-learning. These factors were derived from the literature, interviews with e-learning project leaders, and analysis. Twelve semistructured interviews were conducted and analyzed in order to find out the best success factors to implement e-learning. These factors are divided into two categories: "must-have" factors and "nice-to-have" factors. The must-have factors include: useful and easy to use e-learning tools, marketing, management support, the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 12 publications
0
20
0
4
Order By: Relevance
“…In research articles, there can be found several forms of organizational support for employees' learning: manager support (Karahanna & Straub, 1999;Roca & Gagné, 2008;Sela & Sivan, 2009), colleague support (Greer et al, 1998;Roca & Gagné, 2008), institutional policy support (Liu, Huang, & Lin, 2012), and infrastructural support (Liu et al, 2012;Wild et al, 2002).…”
Section: The Forms Of Organizational Support For Employee Engagement mentioning
confidence: 99%
“…In research articles, there can be found several forms of organizational support for employees' learning: manager support (Karahanna & Straub, 1999;Roca & Gagné, 2008;Sela & Sivan, 2009), colleague support (Greer et al, 1998;Roca & Gagné, 2008), institutional policy support (Liu, Huang, & Lin, 2012), and infrastructural support (Liu et al, 2012;Wild et al, 2002).…”
Section: The Forms Of Organizational Support For Employee Engagement mentioning
confidence: 99%
“…System Quality, System Service, and Organizational Benefits Usefulness and ease of use are compulsory for ELS (Sela & Sivan, 2009) and system quality is positively related to service quality (Kettinger, Park, & Smith, 2008). According to the TAM (technology acceptance model), an easy-to-use system gives users a greater perception of usefulness and promotes a positive attitude toward the system, which implies that a system with better quality (such as better response time, reliability, and accuracy) can deliver better services.…”
Section: Institutional Policy (Itp)mentioning
confidence: 99%
“…It is a prerequisite for ELS projects and is essential to sustain a steady development of ELS (Sela & Sivan, 2009;Elliott & Clayton, 2009). Senior managers should display their full support by attending every important meeting, contributing their opinions to the decision-making process, and arbitrating the conflicts between divisions.…”
Section: Pls Path Modeling and Hypotheses Testingmentioning
confidence: 99%
See 2 more Smart Citations